Separate foliar sodium selenate and zinc oxide application enhances Se but not Zn accumulation in pea (Pisum sativum L.) seeds - Malka, Maksymilian; Du Laing, Gijs; Li, Jun; Bohn, Torsten (Frontiers in Plant Science, 2022)
Up to 15% and 17% of the world population is selenium (Se) and zinc (Zn) deficient, respectively. Pea (Pisum sativum L.) is an important staple legume with a high potential for Se and Zn biofortification in seeds. A 2-year pot experiment investigated two pea varieties (Ambassador and Premium) following foliar-applied sodium selenate (0/50/100 g of Se/ha) and zinc oxide (0/375/750 g of Zn/ha) at the flowering stage. Selenate and zinc oxide had minimal overall effects on growth parameters. Zinc oxide did not improve Zn accumulation in both seed varieties, while selenate improved Se accumulation in both seed varieties dose-dependently. Premium accumulated greater amounts of Se in seeds than Ambassador (p < 0.001). Selenium concentrations were highest in seeds of Premium treated with 100 g of Se/ha [7.84 mg/kg DW vs. the control (0.16 mg/kg DW), p < 0.001]. The predominant Se species in Se-enriched seeds was selenomethionine (40%–76% of total Se). Furthermore, a significant (p < 0.01) positive correlation was found between Zn and S concentrations in Ambassador (r2 = 0.446) and Premium (r2 = 0.498) seeds, but not between Se and S. Consuming as little as 55 g/day of pea biofortified by 50 g of Se/ha would cover 100% of the adult RDA (55 µg) for Se. Findings are important for improving foliar biofortification of pea with Se and Zn.